Teacher motivation from a goal content perspective: Beginning teachers' goals for teaching - Mansfield, C.; Beltman, Susan (Pergamon, 2014)
Viewing teacher motivation from a goal content perspective, this paper examines graduating and early career teachers' professional goals. Responses to an open-ended survey question by 332 graduating teacher education students and 162 early career teachers were analysed through a collaborative, inductive-deductive process. Participants nominated eighteen types of professional goals which were categorised as overarching personal, situated and career goals. Cohort differences reveal some statistically significant goal emphases at the graduating and early career stages. A framework is developed, Beginning Teachers' Professional Goals, which has potential future use for examining teachers' goals at particular career stages and contributing to our understanding of teacher motivation.